STRENGTHENING OF SILICON-CARBIDE BY SURFACE COMPRESSIVE LAYER - KIM, YW; LEE, JG (CHAPMAN HALL LTD, 1995)
Silicon carbide ceramics containing 4.7 wt% WC and 0.3 wt% Co were fabricated by hot-pressing with various additives (B, AlN, and polycarbosilane). Addition of WC and Co liquid phase resulted in considerable increase in flexural strength up to 1085 MPa for the 1 wt% AlN, 0.5 wt% B, and 20 wt% polycarbosilane-added specimen. The improved flexural strength was a result of surface compressive layer. The surface compressive layer was introduced by the liquid flow phenomenon during hot pressing.
Keywords: TRANSFORMATION; STRESSES